Diffusion-controlled and concentric growth zoning revealed by phosphorous in olivine from rapidly ascending kimberlite magma, Benfontein, South Africa. (1st December 2019) - Howarth, Geoffrey H.; Gross, Juliane
Abstract: Olivine chemistry has been widely used to track the petrogenesis of mafic and ultramafic magmas from their mantle source to eruption at the surface. A major challenge in these studies is deciphering crystal growth versus diffusion controlled zoning. Here we report a multi-element approach using high-precision electron microprobe techniques to evaluate crystal growth versus diffusion in kimberlitic olivine from the Benfontein kimberlite, South Africa. These results have implications for both the petrogenesis of kimberlite magmas and the understanding of crystal growth and diffusion-based zoning in igneous olivine in general. The Benfontein olivine contain multiple phosphorous (P)-rich and P-poor zones. Core zones are characterized by homogenous low-P (<78 ppm) concentrations, consistent with xenocrystic origins. Gradational changes in Fo, Ni, Cr and other minor/trace elements at core-margins are similarly characterized by constant low-P concentrations that are indistinguishable from the central regions of the core. Olivine P-maps effectively outline the original xenocryst core, whereas gradational margins are interpreted as diffusion controlled zones related to early-stage equilibration of xenocrystic olivine with proto-/kimberlite melt. Multiple P-poor (100–150 ppm) and P-rich (200–450 ppm) concentric, oscillatory zones with inclusions of kimberlitic oxide phases are observed surrounding the low-P xenocrystic cores. Oxide phases change from chromite in the inner zones to ilmenite in the intermediate zones to magnetite-rich spinel in the outer zones of the olivine. The P-zoning corresponds with changes in Fo content implying that stages of crystal growth was preserved by both fast and slow diffusing elements rather than diffusion processes. Elements compatible with olivine (±chromite) crystallization (i.e., Ni and Cr) display a constant decrease across all zones, suggesting that magma mixing is unlikely a controlling process for P-zoning. We interpret P-rich zones to result from stages of solute trapping related of rapid disequilibrium growth driven by extrinsic factors such as changes in pressure-temperature during kimberlite evolution. In contrast, P-poor zones represent stages of equilibrium crystal growth. The outer olivine zones are characterized by an increase in Fo contents up to Fo96, and in conjunction with a change to more Fe 3+ -rich oxides, suggest late stage increase in f O2 . Correlated Fo and P changes in the Benfontein olivine suggest that major element zonation represents an example where crystal growth-induced Fo zoning has been preserved in olivine. Furthermore, P-rich olivine zones preserve evidence for concentric growth rather than common dendritic structures seen in other occurrences. These results have implications for understanding the effect of magma dynamics and changes in pressure-temperature- f O2 conditions on olivine growth in igneous rocks.